MINING HEALTH PROMOTION: A LITERATURE REVISION (Fiep Bulletin - online, 2014)
To identify the scientific production published in indexed bases about Health Promotion (HP), Risks and Diseases Prevention in mining, through the comprehension of the initiatives reported in the sector interventions. Method: Literature Integrative Revision, with search in Health Virtual Library, using as main term the Descriptor Controlled Health Sciences (MeSH) “mining”, followed by ones “primary prevention”, “accidents prevention”, “health promotion” or “promotion in health”. Altogether, it was reached 154 scientific productions. After reviews careful reading, from which were applied the inclusion and exclusion criteria, they reached 14 articles. Results: It was clarified that the majority of the studies was published in english (92.9%) and in the last three years (64.3%). Regarding to the type of research, the greater part was characterized as a case study and applied research (21.5%, each). Considering the central approach, they were framed in three theme approaching: HP strategies and risks prevention (42.9%), occupational risks (42.9%) and health effects (14.2%), with varied contributions to HP field and Risks and Diseases Prevention. Conclusion: In front of so much possibilities, it isn't possible search for implementing HP and prevention actions in mining.
Keywords: Work; Mining; Occupational Risks; Health Promotion; Primary Prevention.